Changes in Antioxidant Activity and Organoleptic Quality of Mixed Fruit Leather during Drying and Storage - Hoang, Quang Binh; Do, Thi Thuy Lien; Le, Trung Thien (Engineering and Technology For Sustainable Development, 2021)
Fruit leather is a dried fruit product made from one or more different fruits and food additives. It not only gets good taste but also contains many valuable antioxidant compounds such as polyphenols, vitamin C. However, these compounds easily are deteriorated under temperature, oxygen, and light during processing and storage. This study evaluated the effect of drying temperature (50; 60, 70℃), and drying time (9-18 hours) on the change of antioxidant compounds as well as the organoleptic quality of fruit leather mix (gac fruit, papaya, aloe vera, passion fruit seeds). Besides, the retention of antioxidant compounds and color of the product under the different packaging such as polyamide (PA) and aluminum-coated polypropylenen (PP) bags during storage evaluated. The results showed that the sample was dried at 60℃ for 15 hours gave the polyphenol content of 321.67 mg GAE / 100g dm, the vitamin C content of 49.30 mg AAE / 100g dm and water activity of 0.54, moisture content of 17.17%. After storing at room temperature for 2 months, the samples were packed in PA and PP had polyphenol retention of 87.23% and 84.42%, respectively; vitamin C retention of 78.96% and 83.67% respectively, ∆E value of 3.41 and 2.07, respectively. Further studies should be carried out to finding a way to improve stability for polyphenol and vitamin C of the sample.